Potensi Senyawa Kimia dari Herba Kelakai (Stenochlaena palustris) sebagai Antikanker: Kajian Molecular Docking - NAFISAH; HANNA HABIBAH; SARMILA; INDAH SETIAWATI; INDAH SAPUTRI; NOER KOMARI (Gunung Djati Conference Series, 2022)
Kelakai herb (Stenochlaena palustris) is a native fern from Borneo that grows wild on peatlands. This plant has been widely developed and is thought to have potential as an alternative to anticancer drugs. . The purpose of this study was to obtain chemical compounds from the antifungal herb that have the potential as anticancer with parameters in the form of Gibbs free energy data and residue interactions with protein and to determine the prediction of the toxicity of ten chemical compounds derived from the gibbon herb. This research method includes preparation of ligands and target protein, as well as docking of ten test compounds with target protein Anaplastic Lymphoma Kinase with swissdock, visualization of docking results using the USCF Chimera program and toxicity analysis using pkCSM and Protox online tool